MgO Nanoparticles-Incorporated PCL/Gelatin-Derived Coaxial Electrospinning Nanocellulose Membranes for Periodontal Tissue Regeneration - Peng, Wenzao; Ren, Shuangshuang; Zhang, Yibo; Fan, Ruyi; Zhou, Yi; Li, Lu; Xu, Xuanwen; Xu, Yan (Frontiers in Bioengineering and Biotechnology, 2021)
Electrospinning technique has attracted considerable attention in fabrication of cellulose nanofibrils or nanocellulose membranes, in which Poly (caprolactone) (PCL) could be used as promising precursor to prepare various cellulose nanofibril membranes for periodontal tissue regeneration. Conventional bio-membranes and cellulose films using in guided tissue regeneration (GTR) can prevent the downgrowth of epithelial cells, fibroblasts, and connective tissue in the area of tooth root but have limitations related to osteogenic and antimicrobial properties. Cellulose nanofibrils can be used as an ideal drug delivery material to encapsulate and carry some drugs. In this study, magnesium oxide (MgO) nanoparticles-incorporated PCL/gelatin core-shell nanocellulose periodontal membranes were fabricated using coaxial electrospinning technique, which was termed as Coaxial-MgO. The membranes using single-nozzle electrospinning technique, namely Blending-MgO and Blending-Blank, were used as control. The morphology and physicochemical property of these nanocellulose membranes were characterized by scanning electron microscopy (SEM), energy-dispersive spectrum of X-ray (EDS) transmission electron microscopy (TEM), contact angle (CA), and thermogravimetric analysis (TGA). The results showed that the incorporation of MgO nanoparticles barely affected the morphology and mechanical property of nanocellulose membranes. Coaxial-MgO with core-shell structure had better hydrophilic property and sustainable release of magnesium ion (Mg2+). CCK-8 cell proliferation and EdU staining demonstrated that Coaxial-MgO membranes showed better human periodontal ligament stem cells (hPDLSCs) proliferation rates compared with the other group due to its gelatin shell with great biocompatibility and hydrophilicity. SEM and immunofluorescence assay results illustrated that the Coaxial-MgO scaffold significantly enhanced hPDLSCs adhesion. In vitro osteogenic and antibacterial properties showed that Coaxial-MgO membrane enhanced alkaline phosphatase (ALP) activity, formation of mineralized nodules, osteogenic-related genes (ALP, collagen type 1 (COL1), runt-related transcription factor 2 (Runx2)) and high antibacterial properties toward Escherichia coli (E. coli) and Actinobacillus actinomycetemcomitans (A. a) when compared with controls. Our findings suggested that MgO nanoparticles-incorporated coaxial electrospinning PCL-derived nanocellulose periodontal membranes might have great prospects for periodontal tissue regeneration.